PSALM 4 – ISAGOGE, EXEGESIS AND THEOLOGICAL INTERPRETATION (PART I) - PAȘCA-TUȘA, Stelian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
In this research paper, we intend to offer the reader the possibility of becoming more familiar with the main types of biblical commentaries through an exegetic exercise centred round Psalm 4. The choice of the supporting text is not at all random since, even from ancient times, the psalms have benefitted from the attention of an impressive number of scholars and have been the beginning of both dialogue and controversy between religions (Christianity and Judaism) and Christian denominations. Throughout the exegetical analysis, we took into consideration the rigors of the Critical approach, which we correlated with the rabbinic and patristic commentaries in order to accomplish a very ample interpretation. Even if these commentators did not entirely agree, rather than bringing to relief their interpretative differences, we tried to underline the common elements existing in the specific manner of interpretation of each exegetical school. Thus, the complexity of this isagogic, exegetical and theological study resides in the fact that it approaches the text of the psalm from a literary, allegorical and spiritual point of view and it can become a hermeneutical paradigm for those who wish to study the Holy Scriptures with scientific and spiritual accuracy.